2018
DOI: 10.1016/j.jpsychores.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Specific, but not general beliefs about medicines are associated with medication adherence in patients with COPD, but not asthma: Cohort study in a population of people with chronic pulmonary disease

Abstract: Beliefs about medicines are important factors predicting future medication adherence in patients with COPD, but not asthma. Physicians should primarily focus on the specific beliefs of their patients in order to diminish medication non-adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 34 publications
1
32
0
Order By: Relevance
“…Two studies reported the possibility of generalizing the findings, as the analyzed sample matched the representative sample. In the included cohort study [ 23 ], confounding factors were identified and addressed, the intervention/exposure was administered as intended, and medication beliefs and adherence were clearly defined and accurately measured. However, the generalization of the results was described as one of the limitations of this article.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies reported the possibility of generalizing the findings, as the analyzed sample matched the representative sample. In the included cohort study [ 23 ], confounding factors were identified and addressed, the intervention/exposure was administered as intended, and medication beliefs and adherence were clearly defined and accurately measured. However, the generalization of the results was described as one of the limitations of this article.…”
Section: Resultsmentioning
confidence: 99%
“…Findings of the 11 reviewed studies are shown in Table 3 . The studies appeared from 1999 to 2020, ten were cross-sectional studies that included surveys or interviews, while only one was a cohort study [ 23 ]. Most of the studies focused on patients with HTN (5 of 11) or DMT2 (5 of 11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the incidence of exacerbation (≥ 2 times) decreased from 35.23-14.77% in the intervention group, significantly lower than that (27.27%) in the control group (P = 0.042). Patients' belief about medicines could be a predictor of adherence [6]. Patients' attitude toward medications also improved during the study period.…”
Section: Firstly We Summarized and Improved The Inhaler Technique Amentioning
confidence: 87%
“…Though disease control could be achieved effectively among many patients through medication [2,3], present treatment of asthma and COPD are not optimal among many patients [4]. Many factors could affect the disease management of asthma and COPD, such as adherence to prescribed medications, technique of using an inhaler, patients' perceptions and patient education [5,6], and disease management failure predominantly due to the incorrect inhaler technique usage of patients [7].…”
Section: Introductionmentioning
confidence: 99%